Effectiveness of rotavirus vaccine against hospitalized rotavirus diarrhea: a case-control study - Ichiharaa, Maria Y. T. (2014)
Rotavirus is one of the leading cause of hospitalization and outpatients visits among children under five years. This study evaluated overall and genotype-specific vaccine effectiveness of oral monovalent rotavirus vaccine (G1P[8] strain) in preventing hospital admission of Brazilian children with rotavirus acute diarrhea. A hospital based case–control study was conducted in five Regions of Brazil using the National Rotavirus Acute Diarrhea Surveillance System from July 2008 to August 2011. A total of 215 cases (aged 4–24 months) admitted with confirmed rotavirus diarrhea were recruited and 1961 controls hospitalized without diarrhea were frequency matched by sex and age group to cases. Two-dose adjusted vaccine effectiveness (adjusted by year of birth and the frequency matching variables)was 76% (95%CI: 58–86) lasting for two years. Effectiveness controlled by the available potential confounders was 72% (95%CI: 44–85), suggesting no appreciable confounding by those factors for which adjustment was made. In a half of the cases the rotavirus genotype was G2P[4] and in 15% G1P[8]. Genotype-specific VE (two doses) was 89% (95%CI: 78–95), for G1P[8] and 76% (95%CI: 64–84) for G2P[4]. For all G1, it was 74% (95%CI: 35–90), for all G2, 76% (95%CI: 63–84), and for all non G1/G2 genotypes, 63% (95%CI:−27–99). Effectiveness for one dose was 62% (95%CI: 39–97). Effectiveness of two-dose monovalent rotavirus vaccine in preventing hospital admission with rotavirus diarrhea was high, lasted for two years and it was similar against both G1P[8] and G2P[4]. Based on the findings of the study we recommend the continued use of rotavirus in the Brazilian National Immunization Program and the monitoring of the early emergence of unusual and novel rotavirus genotypes.